CONTROL OF FAST AND ACCURATE MOVEMENTS (Fiep Bulletin - online, 2012)
The present study analyzed the hypothesis of the independent components of speed and accuracy to control fast and accurate movements. Twelve college students (right-handed) with mean age of 23 years old (SD=2,67) participated in the study. The task was performed moving a computer cursor controlled by a stylus and a digital table aiming spatial targets. It was manipulated the distance between targets, targets widths, and the direction to be tracked by  the cursor. It was verified lower time movement in the condition in which there was no direction change, in comparison to the other conditions (P
Keywords: spatial targets; speed-accuracy; Fitts' law.